Living Lab exploring routinized kitchen practices to reduce cross-sectoral food waste - Anne Clausen; Niels Kristensen; Stine Hansen (Journal of Agriculture, Food Systems, and Community Development)
This article explores the relationship between everyday food ordering practices in municipally operated kitchens in Denmark—referred to here as public kitchens—catering to public institutions, including schools and care homes, and the logistics defined in public procurement agreements to reduce systemic food waste. In Denmark, it is standard practice for public kitchens to order wholesale food at short notice, as per their food procurement contracts. However, this timeframe, with its short ordering deadline (up to 16 hours prior to next-morning delivery) has been found to cause wholesalers to maintain buffer stocks to meet demand, often resulting in excess waste. Using practice theory, we explored cross-sectoral ordering and delivery practices, specifically focusing on the daily rhythms and operations in publicly owned kitchens. Our aim was to establish whether kitchen ordering practices and wholesalers’ supply schedules could be aligned, consequently reducing wholesale waste. A Living Lab approach was employed, engaging seven publicly owned kitchens in Copenhagen. As a participatory research approach, Living Labs actively engage stakeholders in real-world settings while embracing their diverse realities. We conducted 18 semi-structured interviews before, during, and after the Living Lab. To guide our analysis, we applied the three-elements model from practice theory, analyzing the data through situational mapping. The findings provide insights into how the alignment of food procurement practices, through multi-actor involvement and cross-sectoral partnerships, can reduce food waste across the supply chain.